Analyses of infrared FT spectra of asymmetric ozone isotopologue 16O16O18O in the range 950–3850 cm−1. (October 2018) - Barbe, A.; Starikova, E.; De Backer, M.R.; Tyuterev, Vl.G.
Highlights: Fourier transform spectroscopy of 16 O 16 O 18 O between 950 and 3850 cm -1 . 9976 transitions assigned to fifteen vibrational bands. Effective operator modelling of the spectra. Theoretical predictions on the band centers, rotational constants and coupling parameters. Comparison of calculations and observations. Abstract: Fifteen bands of the most abundant asymmetric ozone isotopomer 16 O 16 O 18 O were observed in new spectra generated from various 18 O2 / 16 O2 mixtures in the 950–3850 cm −1 range. These bands were fully analyzed, leading to the assignment of a total of 9976 transitions, corresponding to 7030 upper state rovibrational energy levels. The analyses include also six "dark" vibrational states perturbing upper states of the observed bands through anharmonic and Coriolis resonance coupling. The modeling of very congested spectra simultaneously containing lines of six isotopic species resulted to the root mean squares deviations that vary from 0.001 to 0.003 cm −1 in line positions, not exceeding the experimental accuracy. To this end, two different approaches both guided by the ab initio theory were employed. Below 2500 cm −1, all the interacting vibrational states involved in the usual polyad scheme corresponding to the same total stretching excitation were observed. In these cases all symmetry allowed Coriolis and anharmonic coupling terms were initially predicted from ab initio potential energy surface (PES) using the contact transformation method. The major coupling terms were then held fixed to theoretical values during the least-square fits of the observed transitions in order to avoid correlations among adjusted parameters. Above 2500 cm −1, some bands were too weak to be observed. In these cases, the observations did not permit including complete stretching polyads and we used truncated effective models, for which the theory helped to predict initial values of the band centers, their assignments and vibrational dependence of A v, B v, C v rotational constants. The final comparison of fifteen experimentally detected and ab initio band centers of 16 O 16 O 18 O gave the rms deviation of 0.59 cm −1 . This drops down to 0.09 cm −1 when using the PES that had been empirically optimized to 16 O3 data. The (observed-predicted) rms deviation for A v and B v is very small - about 0.1%. Average deviations for C v are somewhat larger ∼0.8% as they are affected by Coriolis resonances. Effective dipole transition moment parameters were either fitted or estimated from a qualitative comparison of observed and simulated spectra involving overlapping contributions of various isotopic species. The line lists built from data reduction models containing about 51, 100 transitions are provided in Supplementary Materials.